Global Research Trends in Digital Health Applications for Enhancing Hypertension Patient Adherence: A Bibliometric Analysis - Dwi Famili Rahmawati; Dedy Purwito (INTERNATIONAL JOURNAL OF CARE SCHOLARS, 2026)
Background: This study aims to examine global research trends on the use of digital applications for improving adherence among patients with hypertension through a bibliometric approach. Methods: This study employed a bibliometric analysis using a PRISMA-guided systematic approach. Data were retrieved from the Scopus database through a TITLE-ABS-KEY search using Boolean combinations related to hypertension, digital health technologies, and patient adherence. The search covered publications from 2016 to 2025. After duplicate removal, screening, eligibility assessment, and inclusion procedures, 50 articles met the predefined criteria. The selected records were exported in CSV format, and data cleaning and keyword normalization were performed prior to analysis. Bibliometric mapping, including network, overlay, and density visualizations, was conducted using VOSviewer to identify research trends, thematic structures, and keyword relationships. Results: A total of 50 articles were analyzed. The results showed a marked increase in publications after 2019, reflecting growing global interest in digital health applications for hypertension adherence. Network visualization identified patient, medication adherence, and self-management as the most prominent research themes. Overlay visualization indicated a shift from basic mobile-phone–based interventions toward telemedicine, mHealth, and remote monitoring technologies. Density visualization showed that adherence-related topics remain the dominant focus, while nursing-related digital health interventions and integrated monitoring technologies represent emerging areas for future research. Conclusion: This study shows that the use of digital applications plays an important role in improving the compliance of hypertensive patients and continues to develop towards integrating more complex technology. This finding provides a basis for the development of innovative strategies in hypertension management based on digital technology.